Spatial Analysis of Spillover Effects in The Manufacturing Industry: The Influence of Infrastructure and Industrial Estates in East Java Through an Open Data Approach - Byun Jiye Primasrani; Fadly Muhammad Akbar; Muhammad Prabu Dirgantara (East Java Economic Journal, 2025)
The transition from labor-intensive to capital-intensive industries is a key driver of long-term economic growth. East Java Province holds a strong foundation in the manufacturing sector, positioning it as a locomotive of national industrial growth. While local industrial estates contribute to increasing value-added, the concentration of economic activity also carries the risk of widening spatial disparities between regions. This study aims to examine the spillover effects of industrial estates and infrastructure on manufacturing output. Furthermore, it classifies districts and municipalities based on the most significant and promising variables for the development of new industrial zones. The dependent variable used is manufacturing output, while the independent variables include toll road length, the number of Base Transceiver Stations (BTS), Night-Time Lights (NTL), the Human Development Index (HDI), manufacturing investment, manufacturing labor, minimum wage, and an industrial estate dummy. The analytical method employed is spatial analysis using the Spatial Durbin Error Model (SDEM). The results indicate the presence of positive spillover effects from industrial estates, while BTS and NTL have a direct influence on manufacturing output. Conversely, toll road length, HDI, manufacturing investment, and manufacturing labor primarily affect the sector indirectly. Potential areas for future industrial estate development include urban centers such as Kediri City and Malang City.